“Influencia de los circulares de cordon umbilical en el apgar del recien nacido. Hospital iessalud – moyobamba febrero 98 – febrero 99” - Velasquez Carranza, Katia Mireya (2000)
This paper stresses the importance of the asphyxia of the newborn as a serious event that increases morbidity rates in this age group. Is makes the study of them main factors predispose teas, both maternal, obstetric and them inherent to the or ~ or that can play some role in the presentation of the asphyxiation of the newly born, in 1038 births occurred in them services of OB-obstetrics and of Neonatology of the Hospital II IPSS Tarapoto, from the month of August of 1994 until the month of July of 1995; of which 49 newborns presented some degree of suffocation, which is worked with 2 groups, an experimental group constituted by the 49 neonates with asphyxia, and a control group consisting of a similar number of newly born with optimal Apgar (7-10). The analysis of the casuistry in reference was obtained the following important conclusions: frequency of suffocation 4.7 per cent factors as the absence of prenatal care ~ age matern...